THE MORPHOLOGICAL STUDY ON THE ENDOSCOPIC ANATOMY OF RETROTYMPANUM ON CADAVERIC BONES - Dr Lingaraju N; Dr Tejanand K; Dr Sushrutha K P; Dr Rohith C S; Dr Mudassar Ahmed Shariff; Dr Chaitra N (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The anatomy of the retrotympanum is highly complex and variable. Thorough knowledge of endoscopic anatomy is essential for complete clearance of disease from this area leading to good surgical results. The anatomical study with clinical implications aims to study the anatomy of retrotympanum in cadaveric temporal bones. Aims: This study aims to analyse the surgical anatomy of the retrotympanum in human cadaveric temporal bones. Methods: This is a descriptive anatomical study that was done in our hospital for 18 months between 1st November 2018 and 30th April 2020. 20 fresh cadaveric adult wet temporal bones were harvested, dissected and the frequencies of the structural components were noted. Results: In the present study, 56% showed the confluence of the subpyramidal space with the posterior tympanic sinus and 6% showed its confluence with sinus tympani. 22% showed the subpyramidal space being confluent with both posterior tympanic sinus and sinus tympani. 50% had A type, 40% were of type B, 10% had type C sinus tympani. Discussion: Endoscopic exploration of the middle ear might guarantee a very good exposure of these structures, allowing detailed anatomic descriptions of these hidden areas that cannot be completely visualized with a microscope Conclusion: The thorough knowledge of the surgical anatomy of the retrotympanum is a basic prerequisite for complete eradication of disease from the retrotympanum and decrease the incidence of surgical failure or recidivism.